The Social Aspects of Gender-responsiveness in Schools - Indah Wigati (Sawwa: Jurnal Studi Gender, 2019)
Schools are strategic institutions to fight for gender equality. There is one school in South Sumatera that applies the concept of gender, namely SMA 2 Sekayu. This study aims to analyze the social aspects of gender-responsiveness in schools. The approach used is descriptive qualitative phenomenological. The informants consisted of school principals, teachers, students, school committees, and education staff. Data were collected through observation, interviews, documentation and analyzed using an interactive model of analysis consisting of reduction, presentation, and verification. Meanwhile, the social aspects of gender-responsiveness were analyzed through Longwe. The results showed that the implementation of gender-oriented schools on social aspects involved women and men of the school committee. Teachers' and parents’ interactions run well. The school had a puberty management forum for male and female students. The interaction of all school members is in accordance with the concepts of gender equality. But the teacher did not yet have the ability to control and detect sexual harassment against students. To realize gender-responsiveness, all components in the school must have gender sensitivity.